The moderating impact of government policy on the relationship between leadership styles and crisis management in the Kurdistan region of Iraq public sector - Maghdid, Rekurd Sarhang (2021)
Effective leadership styles have had a significant impact on crisis management as an important process to prevent crises, disasters and unexpected risks. Many studies have been conducted on the impact of leadership styles on crisis management in both private and public sectors. Nonetheless, very little research has been conducted to observe the moderation effect of government policy in the relationship between leadership styles and crisis management in general, and especially in the Kurdistan Region of Iraq‘s public institutions. Therefore, employing Crisis Management Theory and Path-Goal Theory, this thesis has evaluated the impact of the KRG policy on the relationship between the leadership styles (namely: transactional, transformational and servant) and crisis management in the KRI public sector. To obtain the research objectives and test the hypothesis, a quantitative research design, cross-sectional survey method was adopted. For this study, a total of 700 questionnaires were distributed to the public institutions of the KRI where a total of 297 completed and valid questionnaires were returned. The collected data was analyzed by SmartPLS 3.3.3 software program. The results of this study supported the hypothesized impact of Transformational and Servant leadership styles on crisis management as well as partial support for moderating the impact of government policy on the relationship between leadership styles, namely transactional and transformational, and crisis management. Nevertheless, a direct relationship between transactional leadership and crisis management as well as the moderating effect was not evident for the association between servant leadership and crisis management. Finally, this research has ended with conclusions explaining theoretical and practical contributions to academicians and practitioners. Thus, the current study recommends that government policy can positively help managers of public organizations to enhance their behaviors and attitudes. Accordingly, the government policies should be more clear and more observed so that managers can confidently deal with crises. It also suggests that leadership styles can play a notable role in controlling, reducing, and dealing with crisis management in the public sector. The results of this study propose for the managers to keep transformational factors as this leadership style is more effective than other leadership styles to influence staff in the crisis time.